2013
DOI: 10.1002/cssc.201200636
|View full text |Cite
|
Sign up to set email alerts
|

Cyanomethylbenzoic Acid: An Acceptor for Donor–π–Acceptor Chromophores Used in Dye‐Sensitized Solar Cells

Abstract: Sensing the sun: Incorporation of a cyanomethyl benzoic acid electron acceptor into donor-π-acceptor sensitizers for dye-sensitized-solar cell is shown to lead to devices with improved conversion efficiency when compared with more widely used cyanoacetic acid acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…This slight bathochromic shift can be attributed to either uneven surface morphology or film thickness at an incident point on the blend surface. Such divergent variations in solution‐processable thin film devices are also common in similar types of photochemical cells where multiple conducting surfaces are coated on top of each other . However, in view of this broad IPCE, good optical profile, and appropriately positioned energy levels, it is anticipated that N5 can also be a suitable acceptor for other electron‐donating, low‐band gap, conjugated polymers and small‐molecule solids.…”
Section: Resultsmentioning
confidence: 99%
“…This slight bathochromic shift can be attributed to either uneven surface morphology or film thickness at an incident point on the blend surface. Such divergent variations in solution‐processable thin film devices are also common in similar types of photochemical cells where multiple conducting surfaces are coated on top of each other . However, in view of this broad IPCE, good optical profile, and appropriately positioned energy levels, it is anticipated that N5 can also be a suitable acceptor for other electron‐donating, low‐band gap, conjugated polymers and small‐molecule solids.…”
Section: Resultsmentioning
confidence: 99%
“…Knoevenagel condensation of the aldehyde groups present on the oligothiophenes is an efficient way of generating a double bond between the π-bridge and an acceptor unit. The use of such condensations is a common strategy to generate metal-free organic dyes for dye-sensitized solar cells [33]. However, the use of the same strategy to develop materials for BHJ photovoltaic devices has been limited [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Others [6] and we [30] have demonstrated that DSSCs based on such electrolyte systems can reach high conversion efficiencies, especially when used in-conjunction with organic sensitizers. Keeping this criterion in mind and to show the suitability of our new sensitizer with a variety of redox shuttles, we further used cobalt-mediated electrolyte (CE) to construct DSSC devices.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…The details of working and counter electrodes preparation, cell assembly, DSSC device fabrication and characterization, and IMVS and IMPS experimental have been reported previously [22,23,30].…”
Section: Device Fabrication and Characterization Of Dye-sensitized Phmentioning
confidence: 99%
See 1 more Smart Citation